Patient satisfaction with neurosurgical care at King Saud University Medical City - Nasser Almujaiwel; Ghadeer Alsager; Sarah Bin Abdulqader; Safdar Malik; Sherif Elwatidy (Wolters Kluwer Medknow Publications, 2020)
Objectives: The objectives of this study were to determine the extent of patient satisfaction with the care provided by the neurosurgery team in our institution. Methods: This cross-sectional study was conducted at King Saud University Medical City (KSUMC) in Riyadh, Saudi Arabia. Adult postoperative neurosurgical patients, who had elective surgery between January 2018 and March 2019, were included. Data were collected over 3 weeks during May 2019 through telephonic interviews. Ninety-three patients were included (47 cranial and 46 spinal cases). Results: A total of 85 questionnaires were completed. Sixty-nine percent of patients who underwent spinal surgeries did not seek a second opinion from another specialist, whereas 81.4% of the patients with cranial pathologies did. The mean for patient satisfaction for the cranial cases was 88.4%. Cranial patients were least satisfied with the consultant's explanations of the procedure and most satisfied with how their privacy was respected. Spinal patients were least satisfied with the availability of the resident and most satisfied with the availability of the nursing staff. Overall, 91.8% of the patients indicated that they were satisfied with the service that they received. Conclusion: The majority of the patients were satisfied with the care provided by the neurosurgery team at KSUMC and with the results of the surgery. The majority of the patients who underwent spinal surgery did not seek a second opinion from another neurosurgeon, whereas the majority of the cranial patients sought a second opinion.